Analisis Faktor-Faktor Yang Mempengaruhi Kinerja Sistem Informasi Akuntansi Studi Kasus Kantor Kecamatan Sawit, Boyolali - Lutfi Apriana; LMS Kristiyanti; M. Hasan Ma’ruf (Jurnal Ilmiah Keuangan Akuntansi Bisnis (JIKAB), 2022)
This study aims to determine the influence of accounting information system factors on the system implemented in the Sawit District Office, Boyolali. This study uses primary data consisting of several independent variables including the influence of user involvement, personal capabilities, top management support, education and training programs and organizational size which will be examined whether it influences the performance of accounting information systems as the dependent variable. This research is a type of quantitative data. The population in this study amounted to 50 employees involved in accounting information systems, so the entire population was used as a sample. This research method includes data analysis methods using data quality tests, classic assumption tests and multiple regression analysis with results showing user involvement, personal capabilities, top management support, education and training programs, organizational size partially or simultaneously affect information system performance accountancy.